Effects of interaction of poplar-wheat intercropping system on soil quality and yield of wheat (Triticum aestivum L.) (Bangladesh Journal of Botany, 2020)
The significantly higher wheat grain yield in open condition i.e. in control was recorded (4.33 t/ha) over to poplar intercropping. Under the poplar plantation, wheat yield significantly affected and paired row plantation (18 × 2 × 2 m spacing) provides significantly higher grain yield and to 5 × 4 m and 10 × 2 m spacing.